2015
DOI: 10.3389/fnbeh.2015.00327
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress During Adolescence Impairs and Improves Learning and Memory in Adulthood

Abstract: HIGHLIGHTS This study tested the effects of adolescent-stress on adult learning and memory.Adolescent-stressed rats had enhanced reversal learning compared to unstressed rats.Adolescent-stress exposure made working memory more vulnerable to disturbance.Adolescent-stress did not affect adult associative learning or reference memory.Exposure to acute stress can cause a myriad of cognitive impairments, but whether negative experiences continue to hinder individual as they age is not as well understood. We determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…This is in agreement with previous studies in the Japanese quail and others species showing that the pre-natal period is a sensitive period to stress that could result in long-term impacts on the phenotype (human and rodents27845, guinea pig46, birds47, chicken4849, Japanese quail6142450, threespine stickleback1051, guppies52). However, in some other species post-natal experience does have a strong effect on individual phenotype (rat9155354, zebra finch445556575859). It seems that the main difference between the species that are more likely affected by pre-natal or by post-natal stress is the degree of development at birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with previous studies in the Japanese quail and others species showing that the pre-natal period is a sensitive period to stress that could result in long-term impacts on the phenotype (human and rodents27845, guinea pig46, birds47, chicken4849, Japanese quail6142450, threespine stickleback1051, guppies52). However, in some other species post-natal experience does have a strong effect on individual phenotype (rat9155354, zebra finch445556575859). It seems that the main difference between the species that are more likely affected by pre-natal or by post-natal stress is the degree of development at birth.…”
Section: Discussionmentioning
confidence: 99%
“…However, early-life stress is likely to have both benefits and costs. Its potential adaptive outcome may depend on the context within which the phenotypic traits are measured, as well as the life-history stage, the environmental conditions and the generation1461516.…”
mentioning
confidence: 99%
“…They have different molecular strategies for responding to hippocampal injury (McPherson et al, ). They are highly sensitive to the long‐term effects of stress (Chaby et al, ; Wong and Marinelli, 2016), and, if maintained on a high fat diet, they have exacerbated emotional memory of negative events, while adults do not (Boitard et al, ). Encouragingly, it has also recently been demonstrated that exercise during adolescence can have a lasting positive effect.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, unpredictable chronic stress during adolescence has been found to have a context dependent long-lasting effect on memory systems. Specifically, it appears that while rats subjected to unpredictable chronic stress showed an enhancement in working memory to the location of a reward at basal levels, this was completely hindered after exposure to a novel acute stressor 7 . Interestingly, all fish groups responded with an increase in bdnf expression to the acute stressor in the Dlv.…”
Section: Discussionmentioning
confidence: 99%